Analisis Tentang Permasalahan Kekinian Yang Timbul Dalam Penyelenggaraan Ibadah Haji - Dwi Ananda; Husnul Khotimah; Nadzani Pramudya Ibni; Rizka Nanda Utari; Wismanto Wismanto (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The problem of Hajj is a public problem, in fact whatever problems arise around Hajj, it has been answered thoroughly by Islamic guidance since the time of Rasulullah Sallallahu 'alaihi wasallam, the sabbath, tabiin and so on until today. The purpose of this article is to highlight the challenges currently faced when performing the Hajj. The writing method used in writing this article is the literature search method (library search). From this discussion it can be concluded that the procedures for performing the Hajj must be in accordance with the requirements, pillars, obligations and sunnah of Hajj. In Islam, the requirements for Hajj include puberty, intelligence, freedom, power (competence), while the pillars of Hajj are ihram or wearing ihram, and nyyat ihram and hajj, Uquf Arafah on the 9th of Zulhija. ;Tawaf, Sai, Taharrul, orderly or alternating Hajj are valid and intended to be accepted by Allah SWT. Currently, there are several problems with the Hajj pilgrimage that Muslims may not be able to avoid. Hajj cannot be separated from banking problems, Hajj allows someone to enter into religious madhhab, delayed menstruation in women, mikot problems, etc.